Comparative Evaluation of Antibacterial Efficacy of Aloe Barbadensis Miller, Camellia Sinensis, Azadirachta Indica and Doxycycline with Sodium Hypochlorite as Root Canal Irrigant against E. Faecalis: An In-Vitro Study (Global Journal of Medical Research, 2019)
Aims and objectives: Successful root canal treatment involves the complete elimination of pathogenic microorganisms from the root canal system. Enterococcus faecalis is one of them which is most commonly detected in asymptomatic persistent endodontic infections. Chemical irrigation of the root canals along with biomechanical preparation helps in the elimination of such microorganisms. Thus, the present study was done to evaluate and compare the antibacterial efficacy of Doxycycline, Camellia Sinensis, Aloe barbadensis Miller, Azadirachta indica and saline with Sodium hypochlorite as an intracanal irrigant against E.faecalis.
Keywords: Enterococcus faecalis; root canal irrigants; doxycycline; sodium hypochlorite; camellia sinensis and azadirachta indica; and aloe barbadensis miller